New appointments for T3, AY 2010-2011 - De La Salle University, Manila (Animo Repository, 2011)
DLSU President Br. Narciso Erguiza FSC announced the new appointments starting third term, AY 2010-2011. Nilo Pacheco was appointed as Executive Vice President for Finance, Arsenio Roldan III as Vice President for Development and Sponsored Research Administration, and Jose Mari Calleja as Associate Vice Chancellor for Campus Services.